Factors influencing rural migrant households’ participation in livelihood activities and income diversification strategies in Southwestern Nigeria - Adeniyi, Omolehin, Ajayi Raphael; John, Ajiboye Akinyele (Asian Journal of Agriculture and Rural Development, 2025)
This study focuses on factors influencing rural migrant households’ participation in livelihood activities and income diversification strategies in southwest Nigeria. A multistage sampling technique was used for the study. This involved purposive selection of Ekiti, Osun, and Oyo states and twenty percent of the rural Local Government Areas (LGAs) in the respective states. Ten percent of wards in each LGA and 40% of migrant households were randomly selected to arrive at 413 respondents. A structured questionnaire was used to collect relevant data for the study. The collected data were analysed using descriptive statistics, estimation of SID, and multinomial logit regression. The findings showed that 72.75% of household heads were males. 76.75% of the respondents were first-generation migrants, with a mean duration of stay of 29.51 years. The SID revealed that income-generating activities among migrants are moderately (0.53) diversified. The primary factor influencing migrant households’ preference for non-farm and off-farm activities over farm activities was the size of their land holdings. The study recommends that government and other stakeholders should adopt strategy to improve access to non-farm and off-farm employment opportunities, particularly in rural areas, by encouraging corporate and private investors to invest in rural areas to solve the problem of unemployment during off-seasons.